Multiliteracies and e-learning2.0 - Marenzi, Ivana (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2014)
This work, concerned with the significance of literacy and multiliteracies in the 21st century, examines pedagogy from the perspective of Web 2.0 tools and the potential of social networks to improve the quality of learning. Drawing on five years research in German and Italian universities, the author investigates different scenarios in which technology can support the learning process. The focus is on online interaction and collaboration from the standpoint of Educational Technology. With this approach, key pedagogical issues are analysed in relation to theoretical models as well as to the specific learning context. The resulting LearnWeb2.0 Design Framework provides a systematic and up-to-date reference and guide for teachers, researchers and developers when discussing course design and learning supports
Description based on publisher supplied metadata and other sources
Keywords: Gesellschaft; Sprache; Computers and literacy; Educational technology; Language and languages -- Computer-assisted instruction -- Research; Language and languages -- Computer-assisted instruction; Language and languages -- Study and teaching -- Computer network resources; Literacy -- Social aspects; E-Learning; Universität